PENGARUH PARTISIPASI ANGGOTA DAN JUMLAH MODAL TERHADAP SISA HASIL USAHA PADA KOPERASI LPN-PULAU MAINAN KABUPATEN DHARMASRAYA TAHUN 2021 - Krisnaldi; Eka Ermawati; Fenisi Resty (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to determine the effect of Participation and Amount of Capital on the SHU of the LPN-Pulau Mainan Cooperative, Dharmasraya Regency. This research uses a quantitative approach. Data collection by the method of questionnaires(questionnaires), observations, interviews and documentation. The population in this study is 146 members. The data obtained in this study were analyzed using multiple linear regression analysis with the SPSS 20 program. The results showed that the Member Participation variabel (X1) had a positive and significant effect on SHU (Y) because the calculated value of 11.126 and the resulting significant value of 0.000. The amount of Capital (X2) has a positive and significant effect on SHU (Y) because the calculated value of 4,290 and the resulting significant value of 0.00, the variabels Member Participation (X1) and Amount of Capital (X2) have a positive and significant effect on SHU (Y) because the calculated F value of 78,116 and the resulting significant value of 0.000. The value of the coefficient of determination is 0.522 which means that it is 52.2% the effect of Member Participation (X1) and Total Capital (X2) on SHU (Y). Based on the results seen from the beta coefficient, the variabel that has the most influence on SHU (Y) is the Member Patrisipation variabel (X1).